Supercapitance performance evaluation of MXene/Graphene/NiO composite electrode via in situ precipitation technique - Sakhi G. Sarwar; Imosobomeh L. Ikhioya; Shahbaz Afzal; Ishaq Ahmad (Hybrid Advances, 2023)
In this study, we synthesize MXene/Graphene/NiO composite via the in situ precipitation technique. The CV plots exhibited redox peaks, which served as evidence of the presence of faradaic processes. We estimated the specific capacitances of MXene (Ti3C2TX), Graphene, and MXene/Graphene/NiO composite at scan rates of 10, 20, 30, 40, and 50 mV/s. The values obtained were 1250, 625, 416, 312, and 250 F/g for MXene, 972, 486, 324, 243, and 194 F/g for Graphene, and 1666, 847, 564, 423, and 338 F/g for the MXene/Graphene/NiO composite. The specific capacitance values obtained from GCD analysis are estimated to be 139.111, 183.244, 276.483, and 558.788 F/g for MXene (Ti3C2TX), Graphene, and MXene/Graphene/NiO composite, respectively. At a current density of 2.0 A/g, the energy densities obtained for MXene (Ti3C2TX), Graphene, and MXene/Graphene/NiO composite are 100.159, 100.159, and 100.159, respectively. The absorption rate of the graphene, MXene (Ti3C2Tx), and MXene/Graphene/NiO composite is between 0.02 and 0.21, 0.92 to 1.69, and 0.32 to 1.19 a.u. respectively. The graphene has a transmittance value of 90.4%, MXene (Ti3C2Tx) has a transmittance value of 10.3%, and MXene/Graphene/NiO composite has a transmittance value of 49.2%. In terms of energy bandgap, the graphene, MXene (Ti3C2Tx), and MXene/Graphene/NiO composite have values of 0.8, 1.59, and 1.75 eV respectively. The synthesized material has specific capacitances that are well-suited for high-performance energy storage devices.